Художественный текст как предмет лингвопоэтического исследования - ЛИПГАРТ, АНДРЕЙ (Stylistyka, 2021)
Linguopoetic analysis is aimed at specifying the role of linguistic elements in creating the artistic effect а literary text produces. То diminish the subjectivity of evaluation one has to think of special metlюds of investigation other than а typological description ofthe way each particular linguistic element functions in а text. Studying the text as а global aesthetic wlюle can bе done with the help of Unguopoetic Confrontation ( comparing texts with fairly the same content and а similar set of linguistic units in order to see the difference in the use of these units) and Linguopoetic Stratitication (subdividing а text into various thematic imaginative strata). Тhese metlюds, as well as the history of linguopoetic studies in Russia, are in the centre ofthe autlюr’s attention in this paper.